Bacterial Colonization of Low‐Wettable Surfaces is Driven by Culture Conditions and Topography. Issue 20 (30th August 2020) - Marguier, Adeline; Poulin, Nicolas; Soraru, Charline; Vonna, Laurent; Hajjar‐Garreau, Samar; Kunemann, Philippe; Airoudj, Aissam; Mertz, Grégory; Bardon, Julien; Delmée, Maxime; Roucoules, Vincent; Ruch, David; et al.
Abstract: Effect of surface low‐wettability on bacterial colonization has become a prominent subject for the development of antibacterial coatings. However, bacteria's fate on such surfaces immersed in liquid as well as causal factors is poorly understood. This question is addressed by using a range of coatings with increasing hydrophobicity, to superhydrophobic, obtained by an atmospheric plasma polymer method allowing series production. Chemistry, wettability, and topography are thoroughly described, as well as bacterial colonization by in situ live imaging up to 24 h culture time in different liquid media. In the extreme case of superhydrophobic coating, substrates are significantly less colonized in biomolecule‐poor liquids and for short‐term culture only. Complex statistical analysis demonstrates that bacterial colonization on these low‐wettable substrates is predominantly controlled by the culture conditions and only secondary by topographic coating's properties (variation in surface structuration with almost constant mean height). Wettability is less responsible for bacterial colonization reduction in these conditions, but allows the coatings to preserve colonization‐prevention properties in nutritive media when topography is masked by fouling. Even after long‐term culture in rich medium, many large places of the superhydrophobic coating are completely free of bacteria in relation to their capacity to preserve air trapping. Abstract : The interface of low‐wettable and superhydrophobic coatings with bacteria is investigated when immersed in liquid. Aside from the conditions favorable for reducing the colonization, causal factors are determined by GLMM‐based statistical analysis. The biointerface is controlled by culture conditions and secondary by surface topography. Air trapping plays a role on a local scale, preserving bacteria‐free areas even in clogging conditions.